2015
DOI: 10.1080/15222055.2015.1094159
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Intercohort Cannibalism in Mixed‐Size Cultures of Food‐Size and Fingerling Channel Catfish × Blue Catfish Hybrids Grown in Ponds

Abstract: Female Channel Catfish Ictalurus punctatus × male Blue Catfish I. furcatus hybrids are normally harvested by seining single-batch pond or split-pond production systems in fall or winter. Ponds are typically restocked with fingerlings without draining. There is concern that without completely draining the pond after harvest, food-size hybrids that escape seining may cannibalize restocked fingerlings. The purpose of this study was to determine if such hybrid fingerlings stocked after the fall harvest would be ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Survival averaged 90.0% overall (Table ); although survival was slightly higher in ponds stocked with graded fingerlings, it was not significantly different between treatments ( P = 0.11). Previous research with hybrid catfish has shown no evidence for intracohort cannibalism (Torrans and Ott ); therefore, we assumed that this difference was a random effect unrelated to treatment. The survival seen in this study was within the range of survival rates reported in other studies of hybrid catfish (Green et al.…”
Section: Resultsmentioning
confidence: 99%
“…Survival averaged 90.0% overall (Table ); although survival was slightly higher in ponds stocked with graded fingerlings, it was not significantly different between treatments ( P = 0.11). Previous research with hybrid catfish has shown no evidence for intracohort cannibalism (Torrans and Ott ); therefore, we assumed that this difference was a random effect unrelated to treatment. The survival seen in this study was within the range of survival rates reported in other studies of hybrid catfish (Green et al.…”
Section: Resultsmentioning
confidence: 99%
“…(1999) reported numerous instances of cannibalism in tanks and ponds when fingerlings were stocked with larger Channel Catfish up to 374 g. There has been limited published research conducted on the foraging habits of hybrid catfish in commercial ponds due to their relatively new introduction to the catfish industry (Torrans and Ott 2016). A study conducted by Torrans and Ott (2016) stocked hybrid catfish fingerlings with market‐sized fish that were missed from the first production cycle and found no instances of cannibalism. Mortality rates were similar to fingerlings stocked in ponds without larger fish.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no overwinter studies have been published on hybrid catfish, ♀ Ictalurus punctatus × ♂ Ictalurus furcatus , in split ponds. Farmers attempt to harvest all hybrid catfish from these systems before the onset of winter (Torrans and Ott ). However, it is known that catfish in traditional ponds often lose weight overwinter, especially when not fed (Okwoche and Lovell ; Nanninga et al ).…”
Section: Discussionmentioning
confidence: 99%